Upward Ingratiation Outside the Workplace and Supervisor’s Human Resource Decisions: Moderating Effect of Zhongyong Thinking - Sun, Hui; Guo, Haibing; Wang, Kai; Sun, Ling; Wang, Lu (Frontiers in Psychology, 2021)
Based on the theory of social exchange and impression management, this paper focuses on the impact of upward ingratiation outside the workplace on supervisors’ human resources decisions in Chinese context and the mechanism behind this impact. Data were collected from 252 supervisor-subordinate dyads in four manufacturing firms. The results demonstrate that: 1) Supervisors hold a more favorable view of upward ingratiation outside the workplace; 2) Upward ingratiation outside the workplace has a positive effect on the superior's “chance of promotion” and “bonus allocation” (except participation in the decision-making) decision, and Leader-member Exchange (LMX) plays a mediation role in this influence, especially, 3)Zhongyong Thinking（ZYT） moderates the relationship between LMX and supervisors’ “chance of promotion” and “bonus allocation” decisions. This is one of the first empirical studies that examine the validity of subordinates’ upward ingratiation outside the workplace from the perspective of superiors’ ZYT. This paper plays an important role in highlighting the effect of ZYT on the ingratiation behavior.